Drug Correction of Vascular Remodeling in Patients with Hypertension: Results of 52-Week Prospective Study ARTERIA-AG - O. V. Fedorishina; K. V. Protasov; A. M. Torunova (Рациональная фармакотерапия в кардиологии)
Aim. To study the long-term dynamics of vascular remodeling in patients with hypertension and high and very high cardiovascular risk when statin is added to antihypertensive therapy with a fixed combination of calcium antagonist and angiotensin converting enzyme (ACE) inhibitor.Material and methods. Hypertensive patients (n=75) with high and very high cardiovascular risk (age 51.5 [44;58] years) were included in the study. Patients were randomized into two groups. The first group (n=36) received a fixed combination of amlodipine and lisinopril in starting dose of 5/10 mg/day. The second group (n=39) received the same antihypertensive therapy and additionally rosuvastatin (20 mg/day). The follow-up period was 52 weeks. The effect of therapy on the following parameters was evaluated: level of office and average daily blood pressure (BP), central BP in the aorta, augmentation index (AIx), pulse wave velocity (PWV), endothelium-dependent brachial artery vasodilation, carotid intima-media complex thickness, carotid arteries plaque height, and blood lipid profile indicators.Results. A significant decrease in office and average daily BP was found in both groups: from 171.5 (152;194)/104.5 (97;112) to 140.0 (129;154)/87.0 (83;95) mm Hg and from 142.1 (135;153)/86.7 (83;97) to 124.6 (119;133)/76.5 (73;80) mm Hg, respectively, in the 1st group; from 169.5 (160;190)/103.5 (95;109) to 135.0 (125;141)/83.0 (77;88) mm Hg and from 139.9 (136;152)/86.2 (80;92) to 125.1 (118;134)/74.0 (70;81) mm Hg, respectively, in the 2nd group (p<0.001 for all changes). The frequency of reaching the target office BP level was higher in the 2nd group (p=0.031). Significant decrease in total cholesterol by 33.1% and low-density lipoprotein cholesterol by 50.0% was observed in the group 2. Central BP in the aorta decreased in both groups; the degree of central BP reduction did not differ significantly. AIx decreased from 36.5 (24;41)% to 25.0 (15;36)% (p=0.04) in the 1st group and from 36.0 (30;41)% to 24.0 (20;32)% in the 2nd group (p<0.0001) with a more pronounced decrease in AIx after 24 weeks of therapy (-4.8% and -9.4%, respectively, p=0.036). This trend continued at the end of the observation (-6.4% and -10.8%, respectively, p=0.08). Carotid-femoral and carotid-radial PWV decreased only in the 2nd group from 9.5 (8.2;10.7) to 8.3 (7.6;8.9) m/s (p=0.003) and from 9,6 (8.5;10.6) to 8.4 (7.9;9.3) m/s (p=0.01), respectively. A significant decrease in the thickness of the intima-media from 1.08 (1.0;1.2) to 1.02 (0.9;1.1) cm (p<0.0001) and the height of the plaque from 2.2 (2,2;1.7) to 2.1 (2.1;1.7) mm (p=0.001) was found in the 2nd group.Conclusion. Addition of rosuvastatin to the fixed combination of amlodipine and lisinopril in treatment of hypertensive patients with high and very high cardiovascular risk was accompanied by a more frequent (compared with amlodipine and lisinopril only) achievement of the target office BP level and more pronounced reduction in the following indicators: augmentation index, carotid-femoral and carotid-radial PWV, intima-media thickness, plaque height, total cholesterol and low density lipoprotein cholesterol blood levels.